Dependences of Discharge Capacity, Retention of Discharge Capacity, Average Discharge Voltage and Energy Density, and Rate Capability on the Composition of xLi2MnO3-yLiNi1/2Mn1/2O2-(1-x-y)LiNi1/3Co1/3Mn1/3O2 Li-rich Solid-Solution Cathode Materials for Li-Ion Battery. (6th January 2017) - Tsuda, Takashi; Kokubun, Hayato; Asaoka, Yuki; Miyamoto, Koki; Mochizuki, Yasumasa; Gunji, Takao; Tanabe, Toyokazu; Kaneko, Shingo; Ohsaka, Takeo; Matsumoto, Futoshi
Abstract : A great deal attention has recently been focused on the Li-rich solid-solution layered oxide cathode material Li2 MnO3 -Li M O2 (LLO, M = Co, Ni, etc.), which exhibits a discharge capacity of more than 200 mAhg -1 when operated above 4.6 V for lithium ion battery. In this study, in order to find the optimal composition of the LLO exhibiting high cathode performance, which are composed of Li2 MnO3, LiCo1/3 Ni1/3 Mn1/3 O2 and LiNi0.5 Mn0.5 O2, the selected 75 samples having different composition were synthesized under identical preparation conditions and the dependence of the performance of the cathode material on the percentages of Li2 MnO3, LiCo1/3 Ni1/3 Mn1/3 O2 and LiNi0.5 Mn0.5 O2 in the LLO samples was examined under same experimental conditions in the viewpoint of discharge capacity, retention of discharge capacity, average discharge voltage, energy density and rate capability. In each viewpoint, using ternary phase diagrams, the dependence of each property on the percentages of Li2 MnO3, LiCo1/3 Ni1/3 Mn1/3 O2 and LiNi0.5 Mn0.5 O2 in the LLO samples was evaluated. Based on the results obtained, it was comprehensively concluded that Li[Ni0.208 Li0.183 Co0.033 Mn0.575 ]O2 (55% Li2 MnO3 -35% LiNi1/2 Mn1/2 O2 -10% LiNi1/3 Co1/3 Mn1/3 O2 ) possesses the best composition as cathode material for LIBs.